A retrospective analysis of the effectiveness of anterior pelvic organ prolapse repair with Prolift versus Elevate vaginal mesh. Issue 2 (23rd August 2017) - Barros‐Pereira, Isabel; Valentim‐Lourenço, Alexandre; Fonseca, Andreia; Melo, Bruna; Henriques, Alexandra; Ribeirinho, Ana
Abstract: Objective: To compare the effectiveness of anterior pelvic organ prolapse (POP) repair using Prolift (Ethicon, Somerville, NJ, USA) or Elevate (American Medical Systems, Minnetonka, MN, USA) vaginal mesh at 12 months of follow‐up. Methods: A retrospective study was undertaken using the records for the first 50 Prolift procedures in 2007–2009 and the first 50 Elevate procedures in 2013–2015 performed at a tertiary urogynecology unit in Lisbon, Portugal. Postoperative follow‐up occurred at 3, 6, and 12 months. The primary outcome was surgical efficacy using subjective and objective measures (vaginal bulge symptoms and POP quantification system according to the Weber criteria, respectively) at 12 months. Results: Improvement according to the Weber criteria was noted for 10 (25%) of 40 women in the Prolift group and 21 (48%) of 44 in the Elevate group at 12 months ( P= 0.032). Additionally, the Ba point was higher with Elevate than with Prolift (−2.2 ± 1.1 vs −1.5 ± 1.5; P= 0.031). Vaginal bulge symptoms were reported at 12 months by 7 (18%) women in the Prolift group and 3 (7%) in the Elevate group ( P= 0.021). Conclusion: Differences in anatomic results were apparent between the two vaginal mesh groups 12 months after surgery. Abstract : Differences in postoperative anatomic results were detected at 12 months after use of Elevate versus Prolift vaginal mesh for anterior pelvic organ repair.